2014
DOI: 10.1136/jnnp-2014-308401
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with occlusions of the internal carotid artery or the main stem of the middle cerebral artery with NIHSS score of less than 5: comparison between thrombolysed and non-thrombolysed patients

Abstract: Non-thrombolysed patients with mild deficits and large vessel occlusion deteriorated significantly more often within 3 months than thrombolysed patients. Symptomatic intracerebral haemorrhages occurred in less than 5% of patients in both groups. These data suggest that thrombolysis is safe and effective in these patients. Therefore, randomised trials in patients with large vessel occlusions and mild or rapidly improving symptoms are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 27 publications
5
66
2
Order By: Relevance
“…The general approach to perform thrombolysis at our center has been described previously. [10][11][12] Intravenous thrombolysis in our institution was performed according to international and institutional guidelines. 13,14 Our bridging group received either full dose (0.9 mL/kg body weight) or two-thirds dose (0.6 mL/kg body weight) intravenous tPA within 4.5 hours after symptom onset.…”
Section: Methodsmentioning
confidence: 99%
“…The general approach to perform thrombolysis at our center has been described previously. [10][11][12] Intravenous thrombolysis in our institution was performed according to international and institutional guidelines. 13,14 Our bridging group received either full dose (0.9 mL/kg body weight) or two-thirds dose (0.6 mL/kg body weight) intravenous tPA within 4.5 hours after symptom onset.…”
Section: Methodsmentioning
confidence: 99%
“…While historically thought to be a relatively benign condition, more recent data have shown that even these putatively minor strokes, if untreated, lead to higher rates of early neurologic decline, requiring rescue thrombectomy in up to 40% of patients, as well as lower rates of favorable clinical outcomes and independence, compared to patients receiving thrombolysis, ET, or both, with the greatest trend towards poor outcomes amongst untreated patients with an NIHSS score of 5-7 [5,8,15,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Nearly one-third of patients are not treated with intravenous tPA due to mild or rapidly improving symptoms [3,4]. Previous reports have addressed the potential benefit of intravenous tPA and/or ET for low NIHSS score given the outcomes of untreated patients, with the greatest potential for benefit amongst those patients with lower symptom severity and imaging-proven LVOS; however, the data on treated cohorts are limited by small sample sizes and the inclusion of patients with lacunar disease [5,6,7,8,9,10,11]. Thus, we set out to evaluate the clinical and imaging outcomes of a cohort of endovascularly treated LVOS patients presenting with initial mild symptoms (NIHSS score ≤8).…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to the fragile collateral circulation in patients with MIS and LVO, their clinical symptoms could worsen gradually in the short term, and they may finally have severe dis-ability, so timely endovascular recanalization remains critical. [8][9][10][11] However, further studies of high quality are needed to confirm the efficacy and safety of thrombectomy for these patients.…”
mentioning
confidence: 99%